The Effect of Green Infrastructure Investment, Capital Structure, and Operational Efficiency on Financial Performance of Companies in Central Java - Loso Judijanto; Joni Hendra; Eva Yuniarti Utami; Andri Triyantoro (Westscience Press, 2024)
This study investigates the influence of green infrastructure investment, capital structure, and operational efficiency on the financial performance of companies operating in Central Java. A quantitative research approach was employed, utilizing survey data collected from 173 companies across various industries. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with hypothesis testing conducted to assess the significance of the relationships between the variables. The results indicate significant positive associations between green infrastructure investment, capital structure, operational efficiency, and financial performance. Specifically, companies that prioritize sustainability initiatives, maintain optimal capital structures, and enhance operational efficiency tend to achieve superior financial performance outcomes. These findings highlight the multidimensional nature of value creation within organizations and underscore the importance of integrating environmental and operational considerations into strategic decision-making processes. The implications of the study extend to policymakers, business leaders, and stakeholders seeking to enhance the financial sustainability and resilience of companies in Central Java.